Karst Rock Relief of Qara and White Desert (Western Desert of Egypt) - Knez, Martin; Slabe, Tadej; Torab, Magdy; Fayad, Noura (Acta Carsologica, 2023)
The karst rock relief clearly reveals the ways in which the karst surface and caves have been shaped and how they have developed. The oldest traces are the rock features of old karst caves, which were formed under climate conditions entirely different from the current ones, i.e., in the Pleistocene, and which have been dry for a longer period of time. Today, the wind is the prevailing factor in shaping the rock on the surface and in the karst of the White Desert near Farafra in particular, where we can witness the development of an entire range of wind rock features which helps us sort and classify them logically. However, in the wadis near the Qara Oasis a unique rock relief is forming, in which traces of water flow and dissolution of the rock under the sandy deposits are utterly predominant. The rainfall volume is low, however, the heavy rainfall events lasting short periods of time are enough to shape the less resistant rock. The rock features dominating the walls are co-shaped by dissolution and aeolian erosion. Crust forms on those parts of the rock surface that come in contact with water. The bare surfaces, on the other hand, are carved out by the wind. In the places where the crust has flaked off, the wind carves out cups.